Invasions Françaises ou les modalités de présence du théâtre français au Portugal - Ana Clara Santos (Carnets)
Ten years after the departure of Napoleon's troops, a certain enthusiasm in this area began to be noticed as a result of the collaboration between managers and theatre halls in Paris and Lisbon. This influence was admittedly marked by the dispute between several theatre companies and the constant renewal of the repertoire in the Portuguese capital’s theatres, and it constitutes a key factor in the new outlook which needs to be addressed in terms of the evolution of cultural history in Portugal at that time. Although the repertoire in the Parisian scene accounted for more than 80% of performances on Lisbon stages, it was above all the import of theatrical practices and some know-how that were to have a measurable impact on the Portuguese theatrical world on the dawn of Romanticism.